2001
DOI: 10.3748/wjg.v7.i5.630
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of cell clones with different metastatic potential from the metastatic hepatocellular carcinoma cell line MHCC97

Abstract: AIM To establish clone cells with different metastatic potential for the study of metastasis-related mechanisms.METHODS Cloning procedure was performed on parental hepatocellular carcinoma (HCC) cell line MHCC97, and biological characteristics of the target clones selected by in vivo screening were studied. RESULTS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 314 publications
(120 citation statements)
references
References 51 publications
6
114
0
Order By: Relevance
“…In our study, we also found that all cases with lymph node metastasis occurred in patients with positive HIWI expression, although sample size bias could not be completely excluded. Moreover, we found that both mRNA and protein levels of HIWI expression were up‐regulated in 3 high metastatic potential HCC cell lines that were isolated from the same parent cell MHCC97 28. Interestingly, HIWI expression was not different among these HCC cell lines with different metastatic potential.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, we also found that all cases with lymph node metastasis occurred in patients with positive HIWI expression, although sample size bias could not be completely excluded. Moreover, we found that both mRNA and protein levels of HIWI expression were up‐regulated in 3 high metastatic potential HCC cell lines that were isolated from the same parent cell MHCC97 28. Interestingly, HIWI expression was not different among these HCC cell lines with different metastatic potential.…”
Section: Discussionmentioning
confidence: 83%
“…C, P > .05). Furthermore, we examined the SIN1 expression in 6 liver cell lines, including a normal liver cell line (L02 cells), and 5 HCC cell lines with different metastatic potential (HepG2, MHCC97‐L, MHCC97‐H, SMMC‐7721, and HCCLM3) . Either real‐time qRT‐PCR or western blot showed that the SIN1 expression levels were significantly higher in HCC cell lines than those in normal liver cells (LO2) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a metastatic human HCC tumor model (LCI-D20) has been developed in our institute based on the formation of tumors in nude mice using a battery of HCC cell lines with median (MHCC97), low (MHCC97-L) or high (MHCC97-H) metastatic potential [1, 2, 3]. MHCC97 tumors showed responses to IFN-α treatment including inhibition of tumor growth, recurrence and metastasis.…”
Section: Introductionmentioning
confidence: 99%